PERKEMBANGAN MORAL SANTRI ANAK USIA DINI - Muniroh, Siti Mumun (IAIN Pekalongan, 2015)
This study intends to explore and analyze the moral development of students of early childhood at boarding school Salafiyah Shafi'ites Pekalongan. The study was focused on three moral development, namely the aspect of moral reasoning, moral feeling, and moral behavior. The research data was obtained through interviews, observation, field notes and documentation. Data analysis use an interactive analysis model introduced by Miles and Huberman. The results of this study are: moral reasoning of students of early childhood show heteronomous morality. Students understand some important points such as justice, stealing, punishment and tolerance. Some students have an understanding that justice, punishment or regulation are something that are governed by a caregiver who has authority and can not be changed. Moral behavior has been demonstrated too by the students early age. Students have been able to show moral behavior, such as following the rules applied in the boarding school. Meanwhile, from the aspect of moral sense, students of early childhood has evolved as embarrassment, empathy and guilt when breaking the rules.